THE HETEROGENEOUSLY CATALYTIC IZOMERIZATION OF N-PENTANE ON ZIRCONIA - Білокопитов, Ю. В.; Новоселов, Є. Ф.; Вознюк, О. В. (Science-based technologies, 2009)
The isomerization of n-pentane on zirconia, sulfated zirconia and promoted with 2.0 wt % Cu sulfated zirconia(Cu/SZrO) has been studied. It was found the influence of hydrogen and oxygen on the n-pentaneisomerization. It is supposed, that isomerization on the Cu/SZrO catalyst it is substantially carried out throughinteraction olefin with the proton acid centres of a surface.